Evaluasi pengendalian internal distribusi BBM dan LPG berdasarkan COSO framework - Triani Tamedia; Jeffry Otniel Rengku; Andreuw Kristian Pantow (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2026)
The distribution of Fuel Oil (BBM) and Liquefied Petroleum Gas (LPG) requires an effective internal control system to ensure operational accountability, accurate subsidy distribution, and high-quality public services. This study aims to evaluate the effectiveness of the internal control system for BBM and LPG distribution at PT Pertamina Patra Niaga Sales Area Retail SulutGo based on the COSO Internal Control–Integrated Framework 2013. A descriptive-evaluative qualitative approach was employed, with data collected through in-depth interviews, observations, and documentation. Data were analyzed using the Miles and Huberman interactive model and an effectiveness assessment based on the 17 principles of the COSO framework. The results indicate that the internal control system for BBM distribution achieved an effectiveness level of 94%, while LPG distribution achieved 88%, both of which fall within the highly effective category. Nevertheless, several areas require improvement, particularly in the documentation of operational training and the coordination of information with external distribution partners. The findings demonstrate that the implementation of COSO components has supported the effectiveness of internal control in energy distribution and provides practical insights for enhancing corporate governance and operational risk management.